The Rickettsia actin-based motility effectors RickA and Sca2 contribute differently to cell-to-cell spread and pathogenicity - Cuong J. Tran; Zahra Zubair-Nizami; Ingeborg M. Langohr; Matthew D. Welch (mBio)
ABSTRACT Rickettsia parkeri is an obligate intracellular, tick-borne bacterial pathogen that can cause eschar-associated rickettsiosis in humans. R. parkeri invades host cells, escapes from vacuoles into the cytosol, and undergoes two independent modes of actin-based motility mediated by effectors RickA or Sca2. Actin-based motility of R. parkeri enables bacteria to enter protrusions of the host cell plasma membrane that are engulfed by neighboring host cells. However, whether and how RickA and Sca2 independently contribute to cell-to-cell spread in vitro or pathogenicity in vivo has been unclear. Using live cell imaging of rickA::Tn and sca2::Tn mutants, we discovered both RickA and Sca2 contribute to different modes of cell-to-cell spread. Compared with Sca2-spread, RickA-spread involves the formation of longer protrusions that exhibit larger fluctuations in length and take a longer time to be engulfed into neighboring cells. We further compared the roles of RickA and Sca2 in vivo following intradermal (i.d.) infection of Ifnar1−/−; Ifngr1−/− mice carrying knockout mutations in the genes encoding the receptors for IFN-I (Ifnar1) and IFN-γ (Ifngr1), which exhibit eschars and succumb to infection with wild-type (WT) R. parkeri. We observed that RickA is important for severe eschar formation, whereas Sca2 contributes to larger foci of infection in the skin and dissemination from the skin to the internal organs. Our results suggest that actin-based motility effectors RickA and Sca2 drive two distinct forms of cell-to-cell spread and contribute differently to pathogenicity in the mammalian host.IMPORTANCERickettsia parkeri, a bacterium in the spotted fever group of Rickettsia species, can be transmitted from ticks to humans, leading to symptoms including fever, rash, muscle aches, and a lesion at the site of the tick bite. During Rickettsia parkeri infection, bacteria invade cells within the animal host, proliferate in the host cell’s cytosol, move using a process called actin-based motility, and spread to neighboring host cells. Rickettsia parkeri is unusual in having two bacterial proteins that mediate actin-based motility. The significance of our research is to reveal that each of these bacterial actin-based motility proteins contributes differently to spread between cells and to the signs of infection in a mouse model of spotted fever disease. Our results are important for understanding the contribution of actin-based motility to mammalian infection by Rickettsia parkeri as well as to infection by other bacterial and viral pathogens that require this process to spread between cells and cause disease.